Wrath of the furies : a novel of the ancient world - Saylor, Steven, 1956- (Saylor, Steven, 1956- Roma sub rosa., 2015)
"The young Gordianus has been waiting out the chaos in Alexandria, with Bethesda, when he gets a cryptic message from his former tutor and friend, Antipater. Now in Ephesus, as part of Mithridates' entourage, Antipater seems to think that his life is in imminent danger. To rescue him, Gordianus concocts a daring, even foolhardy, scheme to go behind enemy lines and bring Antipater to safety. But there are powerful, and deadly forces, at work here, which have their own plans for Gordianus. Not entirely sure whether he's a player or a pawn, Gordianus must unravel the mystery behind the message if he's to save himself and the people he holds most dear"--